Cardiovascular Disease Risk Factor Changes Over 5 Years Among Male and Female US Firefighters. Issue 6 (June 2020) - Smith, Denise L.; Graham, Elliot; Stewart, Donald; Mathias, Kevin C.
Abstract : Objective: To examine changes in measures of cardiovascular health in male and female firefighters over 5 years. Methods: Anthropometrics and biomarkers of cardiovascular health from two occupational medical exams separated by 5 years (2009 to 2016) were examined from a cohort of US career firefighters in Virginia (males, n  = 603; females, n  = 69). Changes over time were tested using paired t -tests and McNemar's tests. Results: At baseline, 29% of males and 10% of females were obese. Body weight and body mass index significantly increased ( P  < 0.05) in males (2.5 ± 0.2 kg) (0.8 ± 0.1 kg·m –2 ) and females (2.5 ± 0.8 kg) (1.0 ± 0.3 kg·m –2 ) over the 5-year period. The prevalence of obesity, hypercholesterolemia, hypertensive medication usage, and high blood glucose significantly increased in males over the 5-year period. Conclusions: While improvements in blood pressure were observed, large percentages of firefighters, particularly males, had cardiovascular disease risk factors that increased over time.